90 Cooling methods of targeted temperature management and neurological recovery after out-of-hospital cardiac arrest. (16th April 2018) - Kim, KH; Shin, SD; Song, KJ; Ro, YS; Kim, YJ; Hong, KJ; Jeong, J; Park, JH; Kim, TH; Kong, SY
Abstract : Aim: The aim of This study is to determine whether the cooling method used in targeted temperature management (TTM) is associated with neurological recovery after out-of-hospital cardiac arrest (OHCA). Methods: Adult OHCA patients transported to emergency departments (EDs) who survived to admission without traumatic etiology and received TTM between January 2008 and December 2016 in Korea were included in the study. Patients without information on neurological status at hospital discharge or without information about the method of targeted temperature management were excluded. Cooling methods were categorized into four groups: external conventional cooling (ECC), such as ice-water spray, fanning and blanket; external device cooling (EDC) using a cooling machine through surface pads; intravascular cooling (IVC) using an intravascular cooling catheter; and intracavitary cooling (ICC) using lavage with ice water. Primary and secondary outcomes were a good cerebral performance scale (CPC) score of 1 or 2 and survival to discharge, respectively. Potential confounders were adjusted in the multivariable logistic regression analysis (reference=ECC). Results: 4, 246 eligible patients were included in the final analysis. There was no significant difference in the neurological outcome of a good CPC score between cooling methods compared with ECC; EDC 1.20 (0.95–1.52), IVC 1.43 (0.90–2.27), and ICC 0.71 (0.46–1.10). The ICC was associated with a poor survival outcome compared to ECC; EDC 0.97 (0.83–1.15), IVC 0.96 (0.78–1.19) and ICC 0.63 (0.43–0.85). In propensity score matching analysis, there was similar results when comparing outcomes. Conclusion: Cooling methods for TTM did not show any significant difference in neurological recovery. Conflicts of interest: There are no conflicts of interest for all authors in this study. Funding: The study was funded by the Korea Centers for Disease Control and Prevention (CDC). The Korea CDC and National Emergency Management Agency (national fire department) have been collaborating to collect OHCA data.